2000
DOI: 10.4098/at.arch.00-49
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of Ctenomys mendocinus (Rodentia) burrows from two habitats differing in abundance and complexity of vegetation

Abstract: Architecture ofBurrow systems of the fossorial rodent Ctenomys mendocinus Philippi, 1869 were studied in the Andean Precordillera. These burrows were linear, with laterals and branches forked off the main tunnel. Their size and architecture did not differ between sexes. Burrows showed a constant heading along the main tunnel, with a mean directional angle close to 0°. Most forks of the main tunnel were originated more than expected at plants, indicating a change of search pattern where plants were encountered.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 29 publications
(48 reference statements)
0
30
0
1
Order By: Relevance
“…Thus it was reported that males trying to encompass more female territories have longer burrows (Reichman et al 1982;Davies and Jarvis 1986;Rosi et al 1996). However, even strong sexual dimorphism may not be reflected in the length and architecture of burrow systems in solitary subterranean rodents (Rosi et al 2000). Higher branching of systems was found at higher population densities (Reichman et al 1982;Cameron et al 1988).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus it was reported that males trying to encompass more female territories have longer burrows (Reichman et al 1982;Davies and Jarvis 1986;Rosi et al 1996). However, even strong sexual dimorphism may not be reflected in the length and architecture of burrow systems in solitary subterranean rodents (Rosi et al 2000). Higher branching of systems was found at higher population densities (Reichman et al 1982;Cameron et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The architecture (linear versus reticular pattern) of burrow systems was related primarily to density and distribution of food supply (Jarvis and Sale 1971;Reichman et al 1982;Heth 1989;Rosi et al 2000;Spinks et al 2000; but see Cameron et al 1988;Andersen 1988). Recently, Le Comber et al (2002) have correlated the higher fractal dimension (= higher rate of reticulation) of burrow systems among bathyergids with sociality and also with life in a mesic habitat, where a greater food supply is expected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This fact is often used when attempting to trap these animals (Jarvis 1991;Zuri and Terkel 1996). They often store excavated soil belowground, in older burrows, reducing the aboveground advertisement of their presence and the predation risk associated directly with mound construction (Sparks and Andersen 1988;Rosi et al 2000). Further antipredatory behaviours were described by Jarvis and Sale (1971) in the silvery mole-rat (Heliophobius argenteocinereus) and in the East African mole rat (Tachyoryctes splendens): During excavation of their burrow systems, they retreated into deep tunnels and plugged their entrances thoroughly with soil, thus walling themselves off physically from a danger and confusing the ''predator''.…”
Section: Introductionmentioning
confidence: 99%